Cross-cultural adaptation, validation and reliability of the Body Area Scale for Brazilian adolescents Adaptação transcultural, validação e confiabilidade da Body Area Scale para adolescentes brasileiros - Maria Aparecida Conti; Maria do Rosário Dias de Oliveira Latorre; Norman Hearst; Aluísio Segurado (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
The aim of this study was to translate, validate and verify the reliability of the Body Area Scale (BAS). Participants were 386 teenagers, enrolled in a private school. Translation into Portuguese was conducted. The instrument was evaluated for internal consistency and construct validation analysis. Reproducibility was evaluated using the Wilcoxon test and the coefficient of interclass correlation. The BAS demonstrated good values for internal consistency (0.90 and 0.88) and was able to discriminate boys and girls according to nutritional state (p = 0.020 and p = 0.026, respectively). BAS scores correlated with adolescents' BMI (r = 0.14, p = 0.055; r = 0.23, p = 0.001) and WC (r =0.13, p = 0.083; r = 0.22, 0.002). Reliability was confirmed by the coefficient of inter-class correlation (0.35, p < 0.001; 0.60, p < 0.001) for boys and girls, respectively. The instrument performed well in terms of understanding and time of completion. BAS was successfully translated into Portuguese and presented good validity when applied to adolescents. O objetivo do estudo foi traduzir, validar e confirmar a confiabilidade da Escala de Áreas Corporais (EAC). Participaram 386 jovens de uma escola particular de ensino. Avaliou-se a consistência interna e a validade de constructo. Para confiabilidade, utilizou-se o teste de Wilcoxon e o coeficiente de correlação intraclasse. A EAC apresentou bons valores na consistência interna (0,90 e 0,88) e foi capaz de discriminar meninos e meninas, segundo o estado nutricional (p = 0,020 e p = 0,026), respectivamente. Correlacionou-se com o índice de massa corporal (r = 0,14, p = 0,055; r = 0,23, p = 0,001) e a circunferência da cintura (r = 0,13, p = 0,083; r = 0,22, p = 0,002). No reteste confirmou-se sua confiabilidade por meio da correlação intraclasse (0,35, p < 0,001; 0,60, p < 0,001), respectivamente para meninos e meninas. Verificou-se boa compreensão e tempo de conclusão. A EAC encontra-se traduzida, apresentando boa validade para aplicação na população adolescente.